Relationship between laboratory biomarkers and ultrasonographic signs of inflammation in patients with rheumatoid arthritis treated with a rituximab biosimilar - A. S. Avdeeva; O. G. Alekseeva; V. V. Rybakova; E. L. Nasonov (Современная ревматология)
Objective: to assess the relationship between laboratory biomarkers and ultrasonographic signs of inflammation in patients with rheumatoid arthritis during therapy with a rituximab (RTM) biosimilar.Patients and methods. 20 patients with definite diagnosis of RA were examined. All patients received 2 infusions of RTM (Acellbia®), at a dose of 600 mg intravenously 2 weeks apart during therapy with methotrexate, non-steroidal anti-inflammatory drugs and glucocorticoids. Clinical and laboratory parameters were analyzed immediately before the start of therapy, and then 12 and 24 weeks after the first infusion of the drug.Results and discussion. By the 24th week of RTM therapy, a good/moderate effect according to the EULAR criteria was registered in 17 (85%) patients; remission according to DAS28 (<2.6) was achieved in 4 (20%) patients, SDAI (≤3.3) – in 2 (10%), CDAI (≤2.8) – in 1 (5%). Prior to the start of treatment, active synovitis was detected in 13 (65%) patients by power Doppler imaging (PD), and in 20 (100%) patients by gray scale scanning. During therapy with the RTM biosimilar, a significant decrease in inflammatory changes in the joints was observed, and by the 24th week after the start of treatment, the median PD was 0.5; active inflammation persisted in 7 (35%) patients. As shown by ROC analysis, the initial level of interleukin (IL) 6 >100.0 pg/ml is associated with the persistence of inflammatory activity according to PD by the 24th week of therapy with the RTM biosimilar, while the sensitivity was 85% and the specificity was 62% (AUC 0.78, 95% CI 0.57–0.99)Conclusion. An association was found between an increased level of pro-inflammatory cytokines, mainly IL6, and the activity of synovial inflammation according to ultrasound data. IL6 is the most promising marker for predicting persistent inflammatory activity based on the results of PD; other analyzed parameters have worse sensitivity and specificity parameters.